Učeče kulture - Vrečer, Natalija (IB revija (Ljubljana), 2011)
Almost all contemporary societies are multicultural. In order to adequately respond to the issues of multiculturalism, multicultural education was developed in some societies. In the article the method of comparative analysisis applied in order to analyse those traditions of multicultural education in the USA, Great Britain and Germany. The contention of the articleis that in Slovenia we can not speak of multicultural education yet, because in recent years we have only developed some foundations for the aforementioned education. Namely, such individual strategies and initiatives are not sufficient, to answer adequately to the questions of multiculturalism,societies have to reform educational systems and transform them in a systematic way. If contemporary societies (including Slovenia) do not develop multicultural education, they can not achieve effective integration of migrants into educational systems and wider societies.
Keywords: cultural pluralism; kulturni pluralizem; intercultural education; interkulturna vzgoja; integracija; integration; priseljenec; immigrant; imigranti; večkulturnost; education; izobraževanje; kulturne razlike